Antibacterial Biodegradable Films from Papaya Peel Flour Enhanced with Morinda citrifolia Extract for Sustainable Packaging - M, Ahmad Gibran; Widya Dwi Rukmi Putri; Rikza Bilqis Zakia; Zeeges Mollic; Kristiadi, Andreas; Shofiatun Nisa’ Tsabitah (Graduate School, Universitas Brawijaya, 2025)
Biodegradable film is a type of plastic that can be degraded easily by environmental microorganisms because it is made from natural polymer materials. In this study, experiments were conducted using papaya peel and noni fruit extract. Papaya fruit is utilized because the high production of papaya fruit leads to high papaya peel waste, which is currently not optimally utilized. Meanwhile, noni fruit is utilized as an antibacterial agent for biodegradable film because it contains anthraquinone, alkaloid, flavonoid, acubin, and alizarin. biodegradable film is expected to be an alternative packaging that can protect food ingredients from bacteria and become environmentally friendly packaging. The purpose of this study is to determine the effectiveness of noni fruit extract on antibacterial activity in biodegradable films and to find the right formulation for making biodegradable films from papaya skin added with noni fruit extract. The tests conducted in this study were mechanical test, solubility test, thickness, and water content, visual quality test, antibacterial activity test, and biodegradation test. biodegradable film showed varying tensile strength and elongation test results. The addition of noni extract was also effective in inhibiting bacterial growth. In addition, the samples showed significant absorbency and weight loss in the biodegradation test, signaling the potential to degrade.